Agronomic, Physiological, and Post-Harvest Aspects of Different Blueberry Cultivars Treated with Silicon - Silva, Thays; Umburanas, Renan Caldas; Garcia, Carla; Bennemann, Gabriela Datsch; Giloni-Lima, Patricia Carla; Rusin, Carine; Sousa, Allison John de; Botelho, Renato Vasconcelos (Comunicata Scientiae, 2023)
The objective of this study was to evaluate the effect of foliar application of silicon in different blueberry (Vaccinium myrtillus) cultivars. The treatments were installed in a factorial design with six replications, and consisted of three different cultivars (Brightwell, Beckblue and Climax) with or without regular application of silicon via foliar, using silicon oxide at 1.5 g L-1. It was evaluated the following plant attributes: leaf area, chlorophyll fluorescence, and phenylalanine ammonia lyase activity, meanwhile the following postharvest attributes were evaluated: fruit number, diameter and weight, yield, pH, content of soluble solids, titratable acidity, contents of phenolic compounds and anthocyanins, and activity of peroxidase. Vegetative development of blueberry plants in response to Si presented higher yield, leaf area, phenylalanine ammonia lyase activity, and higher chlorophyll fluorescence relationships such as maximum photochemical efficiency and PSII potential activity, as well as less stressed plants, especially in cultivars Climax and Brightwell. For post-harvest physicochemical characteristics, silicon foliar application improved fruit weight and diameter for cvs. Beckblue and Climax, and fruit number for cv. Brightwell. All cultivars, in response to silicon application increased the titratable acidity, the levels of phenolic compounds, the level of anthocyanins, whereas peroxidase activity decreased. The performance of the evaluated blueberry cultivars was better through silicon application, with greater performance of vegetative growth, fruit yield, and fruit quality, especially in cultivar Climax, which was the most suitable in terms in of fruit yield in this study.